Comic book for improving the elementary school students' mathematical problem solving skills and self-confidence - Suryatin Suryatin; Sugiman Sugiman (Jurnal Prima Edukasia, 2019)
The study aims at generating a product in the form of comic book and also displaying the feasibility and the effectiveness of the comic book in improving the mathematical problem-solving skills and the self-confidence of the Grade IV students in the Muhammadiyah Elementary School Condongcatur Yogyakarta. The study is a Research and Development initiative (R) with reference to 10 stages that have been developed by Borg Gall. During the conduct of the study, the subjects were the Grade IV students of Muhammadiyah Elementary School Condongcatur Yogyakarta. The results of the study show that: (1) a comic book-based learning media that meet the criteria of feasibility based on the validation results by the material expert, the media expert, the teacher response and the students response have been generated with “Good” category; and (2) the comic book-based learning media that have been generated are effective for improving the students’ mathematical problem-solving skills and also the students’ self-confidence.